Toward better agricultural grey water footprint allocation under economy-resource factors constraint - Mengfei Song; Weijun He; Min An; Xue Fang; Bei Wang; Thomas Stephen Ramsey (Ecological Indicators, 2023)
Evaluating the spatial matching pattern of agricultural water environment and economy-resource factors, identifying the spatial mismatch areas, and optimizing the management of agricultural water pollution on this basis is the key to alleviating the agricultural water crisis and promoting green agricultural production. This article selected the data related to agricultural water pollution and economy-resource factors of 18 cities in Henan Province from 2006 to 2020. First, the agricultural grey water footprint (GWFagri) was calculated, and the spatial matching pattern between GWFagri and economy-resource factors was analyzed where the Gini coefficient and Imbalance Index were applied. Then, based on the areas of spatial mismatch, a multi-objective programming model was introduced to establish three functions of “Maximizing agricultural GDP-Minimizing agricultural water pollution-Minimizing agricultural water resources loss.” The study found that: (1) During the study period, GWFagri and the grey water footprint of the breeding industry (GWFbre) in Henan Province demonstrated a downward trend, while the grey water footprint of the planting industry (GWFpla) has a more stable trend. (2) In general, Gini coefficients between GWFagri and agricultural GDP, as well as that between GWFagri and the planting area were both between 0 and 0.2, with good spatial matching. The spatial mismatch between GWFbre and various economy-resource factors was slightly higher than that of GWFpla. (3) After optimization, GWFagri of Henan Province decreased by 16.04%in 2020. The Gini coefficients between GWFagri and economy-resource factors decreased by 12.261%, 4.470% and 3.157% respectively. The results can provide specific policy recommendations for improving agricultural water pollution and achieving coordinated and unified development of urban economy, ecology, and resources.